2017
DOI: 10.1097/01.aog.0000514760.55963.a5
|View full text |Cite
|
Sign up to set email alerts
|

Is 'Baby-Friendly' Actually 'Mommy-Friendly?' The Baby-Friendly Initiative and Effect on Patient Satisfaction [11O]

Abstract: INTRODUCTION: The Baby-Friendly Hospital Initiative was launched by the World Health Organization in 1991 to encourage breastfeeding. Baby-Friendly USA has specific criteria for “Baby-Friendly” designation. No studies have been reported about patient satisfaction; few show increased breastfeeding rates. METHODS: Patients aged 16 years or older that were cared for and delivered by the resident service were provided anonymous surveys during postpartum vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[23][24][25][26] Additionally, one survey of mothers in a Baby-Friendly hospital (a hospital conforming with practices recommended by the Baby Friendly Hospital Initiative, a global program to encourage breastfeeding and refrain from promoting formula 27 ) found that 26% of formula-feeding mothers felt shamed for the decision to formula feed and 35.7% felt not adequately informed about formula feeding. 28 In a qualitative study, nonbreastfeeding women reported that probreastfeeding messages from health professionals could lead them to feel that not breastfeeding makes them a "bad mother," one who was "denying" or "depriving" her child. As one explained, "breastfeeding […] is pushed down your throat and out of guilt you are made to feel if you don't do it, you are doing your child a mis-justice."…”
Section: The Case For Maintaining Formula Giveawaysmentioning
confidence: 99%
“…[23][24][25][26] Additionally, one survey of mothers in a Baby-Friendly hospital (a hospital conforming with practices recommended by the Baby Friendly Hospital Initiative, a global program to encourage breastfeeding and refrain from promoting formula 27 ) found that 26% of formula-feeding mothers felt shamed for the decision to formula feed and 35.7% felt not adequately informed about formula feeding. 28 In a qualitative study, nonbreastfeeding women reported that probreastfeeding messages from health professionals could lead them to feel that not breastfeeding makes them a "bad mother," one who was "denying" or "depriving" her child. As one explained, "breastfeeding […] is pushed down your throat and out of guilt you are made to feel if you don't do it, you are doing your child a mis-justice."…”
Section: The Case For Maintaining Formula Giveawaysmentioning
confidence: 99%